2015
DOI: 10.1038/cddis.2015.371
|View full text |Cite
|
Sign up to set email alerts
|

Role of two sequence motifs of mesencephalic astrocyte-derived neurotrophic factor in its survival-promoting activity

Abstract: Mesencephalic astrocyte-derived neurotrophic factor (MANF) is a prosurvival protein that protects the cells when applied intracellularly in vitro or extracellularly in vivo. Its protective mechanisms are poorly known. Here we studied the role of two short sequence motifs within the carboxy-(C) terminal domain of MANF in its neuroprotective activity: the CKGC sequence (a CXXC motif) that could be involved in redox reactions, and the C-terminal RTDL sequence, an endoplasmic reticulum (ER) retention signal. We mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 41 publications
2
74
0
Order By: Relevance
“…MANF contains eight conserved cysteines that form four intramolecular disulfide bonds including two in CXXC sequences 28 . Although the CXXC motif can be found in thiol-disulfide oxidoreductase 26, 30 , MANF is not involved in redox reactions. The CKGC disulfide bridge in the MANF C-terminus is crucial for MANF’s neuroprotective activity 30 .…”
Section: Manf Structurementioning
confidence: 99%
See 3 more Smart Citations
“…MANF contains eight conserved cysteines that form four intramolecular disulfide bonds including two in CXXC sequences 28 . Although the CXXC motif can be found in thiol-disulfide oxidoreductase 26, 30 , MANF is not involved in redox reactions. The CKGC disulfide bridge in the MANF C-terminus is crucial for MANF’s neuroprotective activity 30 .…”
Section: Manf Structurementioning
confidence: 99%
“…Although the CXXC motif can be found in thiol-disulfide oxidoreductase 26, 30 , MANF is not involved in redox reactions. The CKGC disulfide bridge in the MANF C-terminus is crucial for MANF’s neuroprotective activity 30 . In addition, the four amino acids, RTDL at the extreme C terminus of MANF (Fig 2) can bind to the KDEL receptors (KDELRs), which is localized primarily in the cis -Golgi, to facilitate the cycling of MANF from the Golgi to the ER 30, 31 .…”
Section: Manf Structurementioning
confidence: 99%
See 2 more Smart Citations
“…It was, therefore, speculated that the cell protection of MANF might be produced by relieving ER stress and modulating UPR (2,13). In recent years, researchers have reported that increased MANF is able to reduce neuronal apoptosis (9,(14)(15)(16). However, the underlying mechanisms that enable cell protection have not been elucidated.…”
mentioning
confidence: 99%